Biomechanical and musculoskeletal changes after flexor tenotomy to reduce the risk of diabetic neuropathic toe ulcer recurrence. Issue 4 (16th December 2021) - Mens, Marieke A.; van Netten, Jaap J.; Busch‐Westbroek, Tessa E.; Bus, Sicco A.; Streekstra, Geert J.; Wellenberg, Ruud H. H.; Maas, Mario; Nieuwdorp, Max; Stufkens, Sjoerd A. S.
Abstract: Objective: To assess the effect of flexor tenotomy in patients with diabetes on barefoot plantar pressure, toe joint angles and ulcer recurrence during patient follow‐up. Methods: Patients with a history of ulceration on the toe apex were included. They underwent minimally invasive needle flexor tenotomy by an experienced musculoskeletal surgeon. Dynamic barefoot plantar pressure measurements and static weight‐bearing radiographs were taken before and 2–4 weeks after the procedure. Results: A total of 14 patients underwent flexor tenotomy on 50 toes in 19 feet. There was a mean follow‐up time of 11.4 months. No ulcer recurrence occurred during follow‐up. Mean barefoot plantar pressure was assessed on 34 toes and decreased significantly after the procedure by a mean 279 kPa (95% CI: 204–353; p < 0.001). Metatarsophalangeal, proximal interphalangeal and distal interphalangeal joint angles were assessed on nine toes and all decreased significantly (by 7° [95% CI: 4–9; p < 0.001], 19° [95% CI: 11–26; p < 0.001] and 28° [95% CI: 13–44; p = 0.003], respectively). Conclusion: These observations show a beneficial effect of flexor tenotomy on biomechanical and musculoskeletal outcomes in the toes, without ulcer recurrence.